THE EFFECT OF EARNING SURPRISE AND EARNING PER SHARE ON STOCK RETURN - Heni Agustina; Rizki Amalia Elfita (Jurnal Bisnis dan Keuangan, 2022)
A lot of investors are currently focusing on corporate earnings information, resulting on stock market reacts more strongly to unexpected earnings. The reaction is caused by several factors such as Earning Surprise (ES) and Earning per Share (EPS). Based on these, the research was conducted to find out how ES and EPS affect on stock return of manufacturing companies listed on Indonesia Stock Exchange in 2016-2018. This research is quantitative descriptive with associative research methods. The data used in this research were annual reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2016-2018. Sampling in this research was conducted using a purposive sampling method. The results showed that simultaneusly and partially EPS and ES variables have no effect